Implikasi Politik Syiah Wilayah Faqih - Habib Akbar Al Apdolah (UIN Sunan Gunung Djati Bandung, 2022)
Mohammad Nafissi, in his article, concentrates on the Imami Shia and discusses its political impact concerning Iran, its main home since the Safavids made it the religion of the kingdom they founded in the sixteenth century. The essential thing in the history of Iran is the collapse of the power of the monarchy through a revolutionary process called the Islamic Revolution of Iran. Ayatollah Khomeini was an important figure in the revolution and offered the concept of a faqih area to regulate religious, social, political, economic, cultural issues, etc.